Climate change over the past 2000 years in Western China - Holmes, JA; Cook, ER; Yang, B (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Western China, defined here as the land falling within the geographical boundaries of the People's Republic of China in the west, south and north, and the approximate eastern extent of the Tibetan and Alaxa Plateaux to the east, occupies an important climatic region, influenced by the Asian and Indian summer monsoons, the mid-latitude westerlies and the dry, cold central Asian winter monsoon. The Tibetan Plateau itself is a prominent topographic feature that exerts major control on regional atmospheric circulation. Previous compilations of meteorological data and documentary sources suggest that western China, and the Tibetan Plateau in particular, is highly sensitive to anthropogenically induced climate change. Temperature increases appear to be greatest at higher altitudes: moreover, precipitation variations seem to have been marked, although spatially complex. The region contains a wealth of information about past climate derived from instrumental, documentary and proxy sources although meteorological time series are generally too short to capture the full range of recent climatic variability. Documentary and proxy sources are therefore important. We review studies of climate change in western China for the past two millennia. Documentary records are complemented by proxy data from ice cores, tree rings, lake sediments, groundwater profiles and glacial geomorphology. Although general patterns of change can be identified, proxy records of past climate are often semi-quantitative at best, open to alternative interpretations and sometimes poorly dated. Despite evidence for marked variations in climate over the past 2000 years, changes during the 20th century, especially in temperature, may have been unprecedented. The density of data points over western China is currently too low for spatial patterns to be identified, especially in precipitation variation. However, there does seem to have been an increase in warming with altitude over the most recent past. (C) 2007 Elsevier Ltd and INQUA. All rights reserved.